Assets Pricing models: Literature Review - RESA NURLAELA ANWAR (Journal of Business Management Education (JBME), 2022)
What is the relationship between risk and the expected return on an anfunding ?The capital asset pricing model (CAPM) provides a framework for answering the query. The CAPM (Sharpe, 1964; Lintner, 1965) marked the birth of asset pricing theory. This model is based on the idea that not all risk affects asset prices. The CAPM model provides insight into the type of risk associated with returns. The CAPM provides a methodology for translating risk into an estimate of expected ROE. Its application continues to generate debate: many scholars argue that the CAPM is based on unrealistic assumptions. This paper describes the key ideas of the CAPM, the empirical history of the CAPM and the implications for the application of the CAPM and the drawbacks of the CAPM. Keywords: capital asset pricing model; CAPM; risk; returns; risk free; market beta; market portfolio.